2007
DOI: 10.1016/j.cardiores.2007.02.033
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc is essential for urokinase plasminogen activator expression on hypoxia-induced vascular smooth muscle cells

Abstract: The results show that c-Myc was essential for hypoxia-induced uPA expression and activity, resulting in VSMC migration and invasion. In addition, Bcl2 enhanced the c-Myc-mediated uPA/MMP-2 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Several other studies have reported the importance of MMPs in PCa cell proliferation, invasion, and metastasis (Quigley et al, 2018;Wegiel et al, 2008) (Wyganowska-Swią tkowska et al, 2019. Of note, we found that hemeinduced c-MYC levels control the expression of uPA, similar to hypoxia-induced uPA expression (Hou et al, 2007). Because of its role in the process of extracellular matrix degradation, uPA is a poor prognostic marker for PCa, and its expression levels have been associated with distant metastasis and tumor progression (Duffy, 2002;Nassir, 2020;Shariat et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
“…Several other studies have reported the importance of MMPs in PCa cell proliferation, invasion, and metastasis (Quigley et al, 2018;Wegiel et al, 2008) (Wyganowska-Swią tkowska et al, 2019. Of note, we found that hemeinduced c-MYC levels control the expression of uPA, similar to hypoxia-induced uPA expression (Hou et al, 2007). Because of its role in the process of extracellular matrix degradation, uPA is a poor prognostic marker for PCa, and its expression levels have been associated with distant metastasis and tumor progression (Duffy, 2002;Nassir, 2020;Shariat et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
“…Under this condition, certain types of ECM-degrading enzymes play a critical role in promoting the migration and subsequent metastasis of cancer cells [1315]. A well-characterized example of such enzymes is the uPA, a serine proteinase which is overexpressed in many human cancers in a manner associated with their malignancy [16, 17]. Therefore, we hypothesized that the stimulatory effect of semaphorin 5A on tumor invasion and migration is associated with the expression of uPA.…”
Section: Discussionmentioning
confidence: 99%
“…The fibrinolytic activity of PAs was analysed by fibrin zymography, as previously described (33). Briefly, the damaged portions of the livers from u-PA +/+ or u-PA -/mice were harvested on day 0 (before the experiment) and days 4 and 7 after photoillumination and homogenised in ice-cold extraction buffer containing 10 mM sodium phosphate buffer, 150 mM NaCl, 1% Triton X-100, 0.1% so-dium dodecyl sulfate, and 0.5% sodium deoxycholate (pH 7.2).…”
Section: Fibrin Zymographymentioning
confidence: 99%